(untitled) (Studia Prawnicze / The Legal Studies, 2004)
W kontekście art. 226 Traktatu ustanawiającego Wspólnotę Europejską jednostka może tylko w pośredni sposób wpłynąć na zachowanie własnego państwa. Pośredni, bowiem ostateczna decyzja, czy nadać skardze dalszy bieg należy do Komisji i to ona będzie wnosiła skargę do ETS-u. Postępowanie przewidziane w art. 226 TWE nie chroni również wprost uprawnień osób fizycznych i prawnych. In the context of Article 226 of the Treaty establishing the European Community, an individual can only indirectly influence the behaviour of his or her own state. The influence is indirect, because the final decision on whether to proceed with a complaint rests with the Commission, and it is the Commission that brings the complaint before the ECJ. The procedure provided for in Article 226 of the TEC also does not explicitly protect the rights of natural and legal persons.